ANALISIS INTEGRASI PASAR MODAL KAWASAN ASIA-PASIFIK (APEC): IMPLIKASI DIVERSIFIKASI INTERNATIONAL - Subhi, Citra Putri; Fitriyah, Fitriyah (Fakultas Ekonomi, UIN Maliki Malang, 2014)
The purpose of this study was to determine the presence of capital market integration in the AsiaPacific region which has implications for portfolio diversification opportunities internationally. This studyuses quantitative methods to the analysis of the model using VECM (Vector Error correction model) with astationary test level level , different stationary , cointegration and correlation . The population is the entirecountry in the Asia -Pacific (APEC) which has a capital markets while the sample is 10 APEC countries whichinclude U.S. state (^ DJIA), Australia (^AORD), HongKong (^HSI), Japan (^ N225), Singapore (^ STI), Singapore(^ KS11 ), New Zeland (^ NZ50), Indonesia (^ JKSE), Malaysia (^ KLSE), Chinese (^ SSEC) . The results ofthese studies demonstrate that there are capital market integration in the Australian state of capital market(^ AORD)- Malaysia (^ KLSE) and Hong Kong (^ HSI )-South Korea (^ KS11) and there are opportunities in thearea of portfolio diversification proficiency level shows that there are 20 pairs market index has a negativecorrelation coefficient.